Investigation of the relationship between fatigue and cognition after stroke - Lagogianni, Christodouli (2017)
Background: Stroke is among the most common causes of disability and stroke survivors may experience cognitive impairment, low mood and fatigue. These three are often associated, as mood and fatigue share some common symptoms and fatigue can also be expressed in a cognitive manner. Fatigue is multifaceted and cannot be easily defined which complicates its measurement. There is a lack of understanding regarding the relationship between fatigue and cognition after stroke and the studies suffer methodological limitations.